Problemy z sacrum w postsekularnym społeczeństwie.Sens budowania świątyń katolickich we współczesnym Poznaniu (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The article is an attempt to describe the phenomenon of building churches in society, which is less and less involved in religious practices. Although the number of people attending Masses is deacreasing, new temples in Poland, specifically in Poznan, are being built. In the article I indicate a number of reasons why they are built. The starting point for the description of this phenomenon is the sacrum and the issue of cases of its marginalization not so much among the society, but inside the temples themselves.